Peranan Filsafat dalam Pendidikan Ilmu Kesehatan (Kajian Ontologi, Epistemologi, dan Aksiologi) - Pauzi, Iswari; Sarjan, Muhammad; Muliadi, Agus; Azizi, Asrorul; Hamidi, Hamidi; Yamin, Muhammad; Muttaqin, Muh. Zaini Hasanul; Ardiansyah, Bakhtiar; Rahmatiah, Rindu; Sudirman, Sudirman; Rasyidi, Mulia; Khery, Yusran (Educatoria : Jurnal Ilmiah Ilmu Pendidikan, 2022)
The basis of education is a universal human ideal. Education aims to prepare the person in balance, unity, organic, harmonious, dynamic in order to achieve the goals of human life. So that in the world of education it still cannot be separated from the role of philosophy in it. Philosophy of education is vitally related to the development of all aspects of teaching. By placing educational philosophy at a practical level, lecturers/teachers can find various solutions to problems in the world of education, including health education. The benefits of educational philosophy for health sciences are expected to be able to provide guidance to educators (lecturers/teachers), so that it will be able to color their behavior in managing the Teaching and Learning Process (PBM). In addition, with the existence of an educational philosophy, pure knowledge or advanced knowledge in the field of health sciences can be obtained to be applied for the recovery of patients based on supporting premises. This literature review aims to look at the influence and relevance of philosophy and health science education studied from the 3 main components of philosophy, namely: Ontology, Epistemology and Axiology.